Pancreatic Tuberculosis with Markedly Elevated CA 19-9 Levels: A Diagnostic Pitfall - Kaur, Manveen (Oman Med J, 2016)
Despite the high prevalence of tuberculosis (TB) in developing countries, isolated pancreatic TB is rare and is usually seen in immunocompromised patients. It presents with non-specific signs and symptoms and may mimic malignancy both clinically and radiologically. Cytologic and histologic confirmation is required to establish the definitive diagnosis. We present a case of a 25-year-old male with a pancreatic mass and markedly elevated serum cancer antigen (CA) 19-9 levels raising the suspicion of malignancy but with a histopathologic picture of TB. This case suggests that clinicians should have a heightened suspicion of pancreatic TB when faced with discrete pancreatic lesions even though elevated tumor markers may indicate malignancy. It is important to perform appropriate diagnostic testing and initiate antitubercular therapy early.